PEMANFAATAN MIKROBA UNTUK MENINGKATKAN PERTUMBUHAN DAN HASIL KEDELAI DI TANAH PESISIR - Abimanyu Dipo Nusantara; Yudhy Harini Bertham; Ahmad Junedi; Hesti Pujiwati; Hartal Hartal (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2019)
[UTILIZATION OF MICROBE TO INCREASE GROWTH AND YIELDS OF SOYBEAN IN COASTAL LAND]. This study aims to obtain the precise combination of variety and biofertilizer to increase soybean productivity in Bengkulu coastal land. The research was conducted from March to July 2017, located at Beringin Raya Village, Muara Bangkahulu Sub-District, Bengkulu. The study was conducted using a split-plot design which was repeated three times. The main plot was two soybean varieties (Grobogan and Wilis). The subplots were two types of biofertilizers, arbuscular mycorrhizal fungi and phosphate solubilizing fungi. The result showed that the seed weight of the Grobogan variety (equivalent to 3.38 tons/ha) was significantly higher than the Wilis variety (equivalent to 2.72 tons/ha). However, the increment of the Wilis variety (equivalent to 1.12 tons/ha) was higher than the Grobogan variety (equivalent to 0.61 tons/ha) according to the description of each variety. The combination of arbuscular mycorrhizal fungi and phosphate solubilizing fungi showed superior performance than arbuscular mycorrhizal fungi or phosphate solubilizing fungi alone. The interaction of Grobogan varieties with a combination of arbuscular mycorrhizal fungi and phosphate solubilizing fungi produced the highest seed weight (equivalent to 3.52 tons/ha) which was statistically similar to the interaction of Grobogan varieties and arbuscular mycorrhizal fungi (equivalent to 3.45 tons/ha). In terms of economics of resources, the use of arbuscular mycorrhizal fungi is not required to be combined with phosphate solubilizing fungi.